Infant and Young Child Feeding Behavior among Working Mothers in India: Implications for Global Health Policy and Practice - Vinay Kumar, MD, MPH; Gunjan Arora; Ish Kumar Midha, MBBS, DCH; Yogender Pal Gupta, PhD (Global Health and Education Projects, Inc., 2014)
Background: The National Guidelines on Infant and Young Child Feeding introduced in 2006 recommended the initiation of breastfeeding immediately after birth, preferably within one hour; exclusive breastfeeding for the first six months; appropriate and adequate complementary feeding from six months of age while continuing breastfeeding; and continued breastfeeding up to the age of two years or beyond. Working women in India constitute a dominant and expanding pool of mothers. There is paucity of research focused on feeding behavior within this group. Method: One hundred and fifty working women answered a structured questionnaire about their demographics, birth history, levels of awareness and practice of feeding guidelines, and perceptions about breastfeeding and counseling. Data analysis was carried out using Microsoft Excel and the Statistical Package for the Social Sciences. Results: Majority of participants belonged to 21-39 years age group, had nuclear families, received college education, and delivered in institutional setups. Gaps were observed between the mother's levels of awareness and practice for different tenets of national guidelines. Higher education, longer maternity leave, higher income, and utilization of counseling services facilitated adoption of optimal feeding behavior. Most women perceived breast milk to be superior to any alternative and favored provision of counseling during last trimester. Conclusions and Global Health Implications: Counseling women on optimal feeding behavior is a potential intervention to convert its awareness into actual practice. The lessons learned from this study can help refine both national and global Mother and Child Health policies and programs.